Complexity and isotropization based extended models in the context of electromagnetic field: an implication of minimal gravitational decoupling - Tayyab Naseer (European Physical Journal C: Particles and Fields, 2024)
Abstract This paper formulates three different analytical solutions to the gravitational field equations in the framework of Rastall theory by taking into account the gravitational decoupling approach. For this, the anisotropic spherical interior fluid distribution is assumed as a seed source characterized by the corresponding Lagrangian. The field equations are then modified by introducing an additional source which is gravitationally coupled with the former fluid setup. Since this approach makes the Rastall equations more complex, the MGD scheme is used to tackle this, dividing these equations into two systems. Some particular ansatz are taken into account to solve the first system, describing initial anisotropic fluid. These metric potentials contain multiple constants which are determined with the help of boundary conditions. On the other hand, the solution for the second set is calculated through different well-known constraints. Afterwards, the estimated data of a pulsar 4U 1820-30 is considered so that the feasibility of the developed models can be checked graphically. It is concluded that all resulting models show physically acceptable behavior under certain choices of Rastall and decoupling parameters.